Diagnosis of critical thinking of elementary school students in Chimbote, Peru - Pérez-Morán, Graciela; Bazalar-Palacios, Janina; Arhuis-Inca, Wendy (Revista Electrónica Educare, 2021)
Objective. To determine the level of development of the critical thinking of the students of the Educational Institutions of primary education of Chimbote. Materials and methods. A descriptive study was carried out in Chimbote, 2016. Critical thinking was evaluated in 250 boys and girls who belong to the sixth grade of primary education in 2016. A questionnaire of 30 questions aimed at addressing the dialogic and substantive dimensions was applied; each question included 5 response options on the Likert scale (1 = total disagreement up to 5 = total agreement). These variables were re-categorized by scaling by percentiles classified into three categories: (a) high, between 150-100 points; (b) medium, between 99-50; and (c) low, between 49-0 points. A descriptive analysis of the critical thinking variable was carried out according to its substantive and dialogic dimensions through tables with their relative and absolute frequencies. Results. There is a negative tendency in the development of critical thinking which is integrated the dimensions of substantive and dialogical, being the lowest level the one that obtained the highest percentage with 54% compared to the high level with 4.4%. Conclusion. There is a deficit of critical thinking in student body students and in for their substantive and dialogical dimensions.